Evaluation of adhesion in polymeric fibre reinforced cementitious composites - Pakravan, H. R. (2012)
In this study adhesion of some polymeric fibres to a cement matrix was evaluated both by a theoretical and by an experimental approach. In common methods adhesion of the fibres to the cementitious materials is determined by pull-out test. This test evaluates the energy failure during the fibre drawing out. This paper analyzes the adhesion theory for fibre reinforced cementitious composites to separate the share of the chemical and mechanical adhesion expressing new parameters, which are effective in the adhesion behaviour. Explanations about how the different fibres, matrix properties, test factors and environmental conditions can affect the adhesion results are given. It was found that for fibre/cement composites the fracture energy due to the interfacial interactions is for several orders of magnitude smaller that the polymeric fibre losses function. By employing adhesion theory, fibre/cement interac- tions are better described by a simple relationship of their surface free energy. Determination of the loss function (energy dissipation) leads us to predict the fibre behaviour in the cement matrix and the selection of the appropriate reinforcement.